Pengaruh kepemimpinan transformasional terhadap kinerja karyawan dan kesuksesan organisasi - Maulidiana, Ade Ega (Maliki Interdisciplinary Journal, 2024)
Transformational leadership plays a crucial role in enhancing employee performance and organizational success. This leadership style not only focuses on short-term outcomes but also emphasizes empowerment, motivation, and employee development through four key components: Idealized Influence, Inspirational Motivation, Intellectual Stimulation, and Individualized Consideration. This study aims to analyze how transformational leadership affects employee performance. The findings indicate that this leadership style has a positive impact on employee engagement, satisfaction, and loyalty, ultimately leading to increased productivity and organizational sustainability. The implementation of transformational leadership is recommended as an effective strategy to create an adaptive and innovative work environment in response to dynamic business challenges.